AB0069 TIE2 signalling induces a pro-inflammatory and pro-angiogenic phenotype in differentiated macrophages, independently of macrophage polarization conditions. (23rd January 2014) - García Pérez, S.; Krausz, S.; Ambarus, C.A.; Malvar Fernandez, B.; Baeten, D.L.; Tak, P.P.; Reedquist, K.A.
Abstract : Background: Angiogenesis, the induction and growth of new blood vessels, has a pivotal role in mammalian embryogenesis and homeostatic processes, as well as in chronic inflammatory diseases like rheumatoid arthritis (RA). Tie2 is a tyrosine kinase receptor that has an essential role in blood vessel remodeling and angiogenesis, through its activation by ligands angiopoietin (Ang)-1 and Ang-2. Tie2 and its ligands are expressed in RA synovial tissue, and we have recently reported that Ang-1 signaling to Tie2 promotes disease persistence and progression in early RA. Several studies have identified a new lineage of proangiogenic monocytes characterized by the expression of Tie2 (Tie2 expressing monocytes-TEMs) required for tumor establishment. Furthermore, Ang-2 induced Tie2 activation of TEMs increases their inherent pro-angiogenic activity. However, the expression and effect of Tie2 signalling on monocyte-derived macrophages (MDM), key effector cells in RA, has not been assessed yet. Objectives: The aim of this study was to examine how differentiation stimuli regulate expression of Tie2 on human MDM, as well as their effects on expression of macrophage angiogenic factors and gene expression responses to Ang-1 stimulation. Methods: Human healthy donor peripheral blood monocytes were differentiated in the presence of pro-inflammatory/classically activating (GM-CSF, interferon- gamma-IFN-γ-), anti-inflammatory/alternatively activating (M-CSF, IL-10) cytokines. Tie-2 expression was analyzed by flow cytometry and quantitative PCR. Macrophage mRNA expression of 84 angiogenic factors in the absence or presence of TNF stimulation, alone or in combination with Ang-1 was analyzed using low density quantitative PCR Array Results: Tie2 protein and mRNA expression was observed under all conditions, but expression levels failed to correspond to pro- or anti-inflammatory phenotypes. Gene expression analysis of angiogenic factors demonstrated distinct expression profiles under each polarization condition, although unsupervised clustergram analysis demonstrated a high relationship between macrophages differentiated in GM-CSF and IFN-γ. TNF stimulation of GM-CSF and IL-10 –differentiated macrophages enhanced induced expression of the pro-inflammatoty cytokines IL-6, IL-8, TNF and IL-12B (p values ranging from <0.05 to 0.0017 for each cytokine) and the chemokines CXCL-2, 3, 9, 10 and 11 (p values ranging from <0.05 to 0.0177 for each chemokine). Ang-1 stimulation significantly synergized with TNF to promote CXCL2 (p=0.05), CXCL-3 (p=0.05), CXCL-9 (p=0.047) and IL-6 expression (p=0.024), as well as a trend towards enhanced CXCL-5, 6, 10, 11, IL-8, TNF and IL-12B expression. Conclusions: Our results demonstrate that Tie2 is functionally expressed by both pro-inflammatory/classically and anti-inflammatory/alternatively activated macrophages. In all cases, Ang-1 stimulation enhances TNF induced pro-inflammatory cytokine and chemokine expression in these cells. These results suggest that Tie2 signaling, in combination with TNF, induces a pro-inflammatory and pro-angiogenic profile in differentiated macrophages, and provides a molecular basis for the role of Ang-1 in promoting disease progression in both early and established RA. Disclosure of Interest: None Declared